Conductive material and preparation method and related application thereof
By using conductive materials combined with PEDOT and SAMs molecular coordination in perovskite solar cells, the problem of poor efficiency and stability of PEDOT:PSS in tin-lead hybrid perovskite solar cells is solved, and efficient and stable hole transmission and cell performance improvement is achieved.
Patent Information
- Application Number
- CN202411722291.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
The existing PEDOT:PSS cannot achieve ideal efficiency and stability in the hole transport layer of tin-lead mixed perovskite solar cells, and the commercial PEDOT:PSS is an aqueous dispersed solution, which is not suitable for the preparation of all perovskite batteries.
The conductive materials that combine PEDOT and SAMs molecules with mutual coordination are directly synthesized by one-pot method to simplify the process steps, avoid metal-based catalyst residues, regulate the energy level of the hole transport layer, and reduce acidity and interface defects.
It realizes efficient and stable hole transmission, reduces open pressure loss and interface defects, improves the performance and stability of perovskite batteries, and is suitable for industrial production.
Smart Images

Figure CN119529246A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of materials, and in particular to a conductive material and a preparation method thereof and related applications. Background Art
[0002] PEDOT:PSS is a hole-transporting conductive polymer widely used in the semiconductor industry. It is composed of a conductive host PEDOT molecule with a large conjugated system and a stabilizer PSS molecule coordinated with each other. The introduction of PSS is mainly to prevent the PEDOT molecule from crystallizing due to the supramolecular effect within the polymer chain, thereby affecting the conductive properties. In addition, the conductivity of PEDOT is largely derived from the hole-hungry environment provided by the aromatic thiophene ring with ultra-high electron density. If there is no appropriate electronic stabilizer, the structure of PEDOT itself will be unstable. Commercial PEDOT:PSS molecules usually use a far excess ratio of PSS molecules to maintain performance. Because PEDOT:PSS molecules have conductive properties comparable to metal oxides and even metals, they are widely used in LED displays, photovoltaic cells and other equipment, and have broad prospects.
[0003] Perovskite solar cells have developed rapidly in recent years, and their efficiency has increased rapidly in the past decade, surpassing traditional silicon-based solar cells, and have a wide range of commercial application prospects. Due to its adjustable band gap, perovskite solar cells have also derived all-perovskite tandem cells. This cell structure enables a single cell to break through the Shockley-Quismey limit, which is the most promising type of perovskite solar cell. Due to the use of two cell stacking processes, all-perovskite tandem cells currently generally use PEDOT:PSS as the hole transport layer of the back cell to protect the front cell from damage during the preparation process and to have a certain encapsulation barrier effect. However, when PEDOT:PSS is used in the hole transport layer of tin-lead mixed perovskite, it cannot achieve ideal efficiency and stability. In addition, commercial PEDOT:PSS is usually a water-dispersed solution, which is also very unfavorable for the preparation of all-perovskite cells. Excessive water vapor will accelerate the rapid degradation of the front cell.
[0004] Current researchers have noticed the many drawbacks of PEDOT:PSS and have taken some measures to modify it. This modification is mainly based on doping. Some researchers have introduced dopamine molecules into PEDOT:PSS to change the energy level of PEDOT:PSS and reduce the acidity caused by the mismatched sulfonate groups of excessive PSS to improve device stability and photovoltaic conversion performance; similar methods include oxalic acid doping modification, benzenesulfonic acid doping modification, etc. In general, this doping modification research method is effective, but because it still relies on PEDOT:PSS as the main body, it does not fundamentally solve the problems of PEDOT:PSS and has little competitiveness in industrial prospects. How to find a simple, cheap hole transport layer material that matches tin-lead mixed perovskite solar cells has become the goal of many researchers.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a conductive material and a preparation method thereof and related applications.
[0007] The present invention is achieved in that:
[0008] In a first aspect, an embodiment of the present invention provides a conductive material, which includes: PEDOT and SAMs molecules; the PEDOT and the SAMs molecules are coordinated and bonded to each other.
[0009] In a second aspect, an embodiment of the present invention provides a method for preparing the conductive material as described in the above embodiment, which comprises: preparing the conductive material using EDOT molecules and SAMs molecules.
[0010] In a third aspect, embodiments of the present invention provide the use of the conductive material described in the preceding embodiments or the conductive material prepared by the preparation method described in the preceding embodiments for use in the preparation of perovskite cells or perovskite cell components.
[0011] In a fourth aspect, an embodiment of the present invention provides a perovskite cell or a perovskite cell assembly, wherein the perovskite cell comprises: a conductive substrate, a hole transport layer, a perovskite active layer, an electron transport layer, a hole blocking layer and an electrode layer; wherein the hole transport layer is prepared using the conductive material described in the aforementioned embodiment or the conductive material prepared by the preparation method described in the aforementioned embodiment.
[0012] The present invention has the following beneficial effects:
[0013] (1) Since SAMs molecules can guide the high-temperature polymerization reaction of EDOT in air, PEDOT:SAMs conductive materials can be directly synthesized by a one-pot method. This greatly simplifies the process steps and avoids the catalyst residue and purification difficulties caused by the use of metal-based catalysts in conventional PEDOT synthesis methods.
[0014] (2) The energy level of PEDOT:SAMs conductive materials will change with the ratio of PEDOT and SAMs molecules. The energy level of the hole transport layer can be adjusted according to the purpose of use to minimize the voltage loss caused by energy level mismatch.
[0015] (3) Only a very small amount of SAMs molecules can make PEDOT:SAMs achieve the same or even higher performance as PEDOT:PSS, which largely prevents the excess uncoordinated acid radicals from remaining. This reduces the acidity of the hole transport layer and avoids acid-induced disintegration of the lower interface. It also optimizes the crystallization rate of perovskite and reduces interface defects.
[0016] (4) Since SAMs are small molecules, on the one hand, compared with PSS, SAMs have almost no strain caused by temperature changes. On the other hand, the flexibility of small molecules allows a certain amount of stress release space. Therefore, the perovskite on PEDOT:SAMs has a lower stress level, which helps to improve stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 A schematic diagram of a process for preparing a PEDOT-based conductive material provided by the present invention;
[0019] Figure 2 The Raman spectra of EDOT, SAMs, and PEDOT:SAMs obtained by the reaction in Example 1 of the present invention;
[0020] Figure 3 The carbon element XPS test results of the three samples of PEDOT, SAMs and PEDOT:SAMs in Example 1 of the present invention are shown;
[0021] Figure 4The oxygen element XPS test results of the three samples of PEDOT, SAMs and PEDOT:SAMs in Example 1 of the present invention;
[0022] Figure 5 is the hydrogen nuclear magnetic resonance spectrum of SAMs, PEDOT and PEDOT:SAMs in Example 1 of the present invention;
[0023] Figure 6 is the carbon NMR spectra of PEDOT and PEDOT:SAMs in Example 1 of the present invention;
[0024] Figure 7 In Example 1 of the present invention Figure 6 Comparison of the carbon spectrum peak position changes of the two substances;
[0025] Figure 8 This is a schematic diagram of the structure of the final product obtained in Example 1 of the present invention;
[0026] Fig. 9 The ESR test results of PEDOT, SAMs, PEDOT:PSS and PEDOT:SAMs in Example 1 of the present invention;
[0027] Fig.10 Comparison of IV curve test results of the perovskite device obtained when four materials, SAMs, PEDOT, PEDOT:PSS, and PEDOT:SAMs, are used as the hole transport layer in Example 2 of the present invention;
[0028] Fig.11 The storage stability of the perovskite device obtained when PEDOT:PSS and PEDOT:SAMs are used as the hole transport layer in Example 2 of the present invention under N2 environment is tested;
[0029] Fig.12 The performance of transport layers with different ratios prepared by using 200 μL EDOT (6 mmol) and different added amounts of SAMs (MEO-2PACz) in a solar cell device in Example 2 of the present invention;
[0030] Fig.13 The performance of the transport layer prepared by heating 200 μL EDOT (6 mmol) and 3 mg SAMs (MEO-2PACz) at 130 degrees Celsius for different time periods in a solar cell device in Example 2 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0032] The abbreviations in this article are all fixed abbreviations in this field. Among them, some of the abbreviations are explained as follows: SEM image: scanning electron image; TEM image: transmission electron scanning image; XRD image: X-ray diffraction image; Mapping image: element distribution map.
[0033] In the existing conductive material PEDOT:PSS, due to the serious excess of PSS molecules, PEDOT:PSS is in an acidic state as a whole. Since the back cell of the all-perovskite stacked battery is usually a tin-lead mixed perovskite battery, this acidity is particularly unfavorable for the stable existence of divalent tin ions, which will lead to acid-catalyzed tin oxidation degradation at the interface, resulting in a rapid decline in battery performance. In addition, the PSS group only considers the stability of PEDOT, without considering the energy level and lattice matching of the tin-lead mixed perovskite. On the one hand, this leads to energy level mismatch between the two, resulting in opening voltage loss; on the other hand, PSS, as a polymer, will produce a large tensile strain that changes with temperature, which will cause stress concentration at the interface. More importantly, PEDOT:PSS contains a large number of uncoordinated carboxyl groups, which will cause the perovskite to crystallize too fast on it, resulting in serious uneven crystallization at the bottom interface. This defect is even visible to the naked eye most of the time. Therefore, when PEDOT:PSS is used in the hole transport layer of tin-lead mixed perovskite, it cannot achieve ideal efficiency and stability. In addition, commercial PEDOT:PSS is usually a water-dispersed solution, which is also very unfavorable for the preparation of all-perovskite cells. Excessive water vapor will accelerate the rapid degradation of the front cell.
[0034] In response to the problems existing in the prior art, the inventors of the present application provide a new conductive material PEDOT:SAMs, which has at least the following advantages: (1) The SAMs molecule itself can guide the high-temperature polymerization reaction of EDOT in an air environment, and during the reaction process, it acts as a catalyst for EDOT polymerization and a stabilizer for PEDOT after polymerization. This allows the conductive material to be directly synthesized using a one-pot method. On the one hand, it greatly simplifies the process steps, and on the other hand, it avoids the catalyst residue and purification difficulties caused by the use of metal-based catalysts in conventional PEDOT synthesis methods. It is green and environmentally friendly and suitable for large-scale industrial production. (2) The energy level of the PEDOT:SAMs conductive material will change with the different ratios of PEDOT and SAMs molecules. The more SAM is added, the lower the energy level is, making it more suitable for materials with low valence bands to transport holes. The type and addition ratio of SAMs can be adjusted according to the purpose of use. For example, for common tin-lead perovskite, the valence band energy level of PEDOT:SAMs can be adjusted to about -5.3 electron volts (corresponding to the ratio of EDOT:SAMs = 20:3) to maximize the energy level of the perovskite material and avoid the turn-on voltage loss caused by energy level mismatch. This property has greatly broadened the application range of PEDOT-based conductive materials; (3) The proportion of SAMs required in the synthesis of PEDOT:SAM is extremely low, about 40 times lower than that of PSS. Only a very small amount of SAMs molecules can make PEDOT:SAMs obtain the same or even higher performance as PEDOT:PSS. This largely prevents the excess uncoordinated acid radicals from remaining. On the one hand, this reduces the acidity of the hole transport layer and avoids acid-induced disintegration of the lower interface; on the other hand, it optimizes the crystallization rate of the perovskite and reduces interface defects; (4) Since SAMs are small molecules, on the one hand, there is almost no strain caused by temperature changes compared to PSS. On the other hand, the flexibility of small molecules allows a certain amount of stress release space. Therefore, the perovskite on PEDOT:SAMs has a lower stress level, which helps to improve stability.
[0035] On the one hand, an embodiment of the present invention provides a conductive material, which includes: PEDOT and SAMs molecules; the PEDOT and the SAMs molecules are coordinated and bonded to each other.
[0036] PEDOT is a polymer of EDOT (3,4-ethylenedioxythiophene monomer).
[0037] SAMs (Self-Assembled Monolayers) molecules are molecules that can be used to construct self-assembled monolayers, usually composed of anchoring groups (functional groups such as phosphate, carboxylic acid, and silicate), carbon chains, and carrier receiving groups (such as carbazole derivatives).
[0038] In some embodiments, the SAMs molecules include any one or more combinations of MEO-2PACz, 3-(9H-carbazol-9-ylpropionic) acid (CPA), 9-carbazoleacetic acid (CAA) and 2PACz.
[0039] In some embodiments, the raw materials for preparing the conductive material include EDOT molecules and SAMs molecules; the molar ratio of the EDOT molecules to the SAMs molecules is 1:0.1-50.
[0040] In some embodiments, the molar ratio of the EDOT molecules to the SAMs molecules can be any one of 1:0.1, 1:0.5, 1:1, 1:2, 1:4, 1:6, 1:8, 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, 1:22, 1:24, 1:26, 1:28, 1:30, 1:32, 1:34, 1:36, 1:38, 1:40, 1:42, 1:44, 1:46, 1:48 and 1:50, or a range between any two of them.
[0041] In some embodiments, the molar ratio of the EDOT molecules to the SAMs molecules can be 10 to 30:3, specifically any one of 10:3, 12:3, 14:3, 16:3, 18:3, 20:3, 22:3, 24:3, 26:3, 28:3 and 30:3 or a range between any two of them.
[0042] On the other hand, an embodiment of the present invention further provides a method for preparing the conductive material as described in any of the above embodiments, comprising: preparing the conductive material using EDOT molecules and SAMs molecules.
[0043] In some embodiments, the preparation method comprises the following steps: Figure 1 :
[0044] Mixing the EDOT molecules and the SAMs molecules in a solvent to obtain a mixed solution;
[0045] The mixed solution is heated to react to obtain a conductive material.
[0046] In some embodiments, the conditions of the heating reaction include: 12 to 240 hours, 70 to 180° C. The time can be any one of 12, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230 and 240 hours or a range between any two thereof. The temperature can specifically be any one of 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175 and 180°C, or a range between any two of them.
[0047] In some embodiments, the preparation method further includes: condensing and refluxing the gas generated by the heating reaction so that by-products can be discharged in a timely manner.
[0048] In some embodiments, the solvent includes any one or more combinations of DMF, DMSO, water, methanol, ethanol and ethyl acetate.
[0049] In some embodiments, the mixing method includes stirring.
[0050] In some embodiments, the stirring speed is 100-1500 rpm, and the speed can be any one of 100, 200, 400, 600, 800, 1000, 1200, 1400 and 1500 rpm or a range between any two thereof.
[0051] In some embodiments, the stirring time is 0.1 to 120 hours, and the stirring time can be any one of 0.1, 1, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110 and 120 hours, or a range between any two of the above.
[0052] In some embodiments, the stirring temperature is 0 to 100° C., and the temperature can be any one of 0, 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100° C. or a range between any two of the ranges.
[0053] In some embodiments, when performing the heating reaction, the preparation method further includes stirring the mixed solution at a constant temperature.
[0054] In some embodiments, the constant temperature stirring speed is 1-4000 rpm, and the speed can be any one of 1, 100, 200, 400, 600, 800, 1000, 1500, 2000, 2500, 3000, 3500 and 4000 rpm or a range between any two thereof.
[0055] The preparation method provided by the present invention is suitable for large-scale, high-quality production of conductive materials, and has the advantages of simple process steps, easy implementation, short preparation cycle, environmental protection, high preparation efficiency, high conductivity and good stability of the product, etc.
[0056] On the other hand, an embodiment of the present invention further provides the use of the conductive material described in any of the foregoing embodiments or the conductive material prepared by the preparation method described in any of the foregoing embodiments in the preparation of a perovskite cell or a perovskite cell component.
[0057] The present invention has no special restrictions on the preparation process of perovskite cells or perovskite cell components. Their structure and preparation process can be obtained and implemented based on conventional technical knowledge in the field. The main invention of this application is to use the conductive material described in any of the aforementioned embodiments to prepare the hole transport layer of the perovskite cell.
[0058] On the other hand, an embodiment of the present invention further provides a perovskite cell or a perovskite cell assembly, wherein the perovskite cell comprises: a conductive substrate, a hole transport layer, a perovskite active layer, an electron transport layer, a hole blocking layer and an electrode layer;
[0059] Wherein, the hole transport layer is prepared by using the conductive material described in any of the foregoing embodiments or the conductive material prepared by the preparation method described in any of the foregoing embodiments.
[0060] In some embodiments, the conductive substrate, hole transport layer, perovskite active layer, electron transport layer, hole blocking layer and electrode layer are arranged in sequence.
[0061] In some embodiments, the thickness of the hole transport layer is 10 to 50 nanometers, specifically any one of 10, 20, 30, 40, and 50 nanometers or a range between any two thereof.
[0062] The present invention has no special restrictions on the preparation process of the hole transport layer, and the existing preparation process of the hole transport layer can be used. In some embodiments, the preparation process of the hole transport layer includes: any one of vacuum evaporation, molecular beam evaporation, dip coating in a solvent, spin coating, rod coating or inkjet printing.
[0063] In some embodiments, the perovskite cell assembly includes a plurality of perovskite cells connected in series.
[0064] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0065] Example 1
[0066] A method for preparing a conductive material PEDOT:SAMs comprises the following steps.
[0067] 200 μL EDOT (6 mmol) liquid was dispersed in 4 mL DMF and stirred continuously at 2000 rpm. Then 2 mg MEO-2PACz molecules (SAMs molecules) were added and stirred thoroughly to completely dissolve the solid until a clear solution was formed.
[0068] The obtained solution was added to a flask, stirred continuously at 3000 rpm and heated in an oil bath at 150°C for 24 hours, and a condensation splitter was set at the reactor outlet for fractionation so that the by-products could be discharged in time. After the reaction was completed, a reaction solution (PEDOT:SAMs conductive material) was obtained.
[0069] The materials prepared in Example 1 and the final device were characterized:
[0070] in, Figure 2 This is the Raman spectrum of EDOT, SAMs, and PEDOT:SAMs obtained by reaction. It can be seen that after the reaction, the wave number is 1460cm -1 The large conjugated carbon chain resonance peak that appears when EDOT polymerizes into PEDOT appears at the position of 450 cm -1 Position and wave number 750~1000cm -1 The resonance signal attributed to deprotonated phosphoric acid appears in the range of , indicating that the SAMs molecule exists in the form of deprotonated phosphoric acid. Due to the need for charge balance, deprotonated phosphoric acid is difficult to exist independently, so it can be inferred that it is combined with some substance.
[0071] Figure 3 and Figure 4These are the XPS test results of carbon and oxygen elements of three samples, PEDOT, SAMs and PEDOT:SAMs. In the carbon spectrum, it can be seen that a new carbon peak appears at a higher binding energy position after mixing PEDOT and SAMs. According to the XPS test principle, the increase in the excitation binding energy of inner-layer electrons indicates the absence of outer-layer electrons, which indicates that the electrons on one or some carbons have been taken away. Combined with the analysis results of Raman spectroscopy, this decrease in electron density is likely caused by the coordination of deprotonated carboxylic acids. Therefore, it is reasonable to infer that SAMs form complexes by combining deprotonated phosphoric acid with carbon on PEDOT, which is actually consistent with the recognized PEDOT:PSS binding mode. Figure 4 The oxygen spectrum can prove that both substances exist in the sample and the peak intensities conform to the rules.
[0072] Figure 5 The three spectra are the hydrogen NMR spectra of SAMs, PEDOT and PEDOT:SAMs. TMS is used as the standard sample and deuterated DMSO is used as the solvent for testing. It can be seen that the characteristic peaks of SAMs and PEDOT are fully present in the test results of PEDOT:SAMs, indicating that the structures of the two are not destroyed, but only combined with each other.
[0073] Figure 6 The two spectra in the figure are the NMR carbon spectra of PEDOT and PEDOT:SAMs. After comparing the chemical shifts of the three carbon peaks ( Figure 7 ) It can be found that one of the carbon peaks has a specific shift to the low field, which indicates that the electron cloud density on this carbon has been weakened. This further confirms the binding site of SAMs and PEDOT on the basis of XPS, so we can get the final structure of the product as follows Figure 8 shown.
[0074] Fig. 9These are the ESR test results of PEDOT, SAMs, PEDOT:PSS and PEDOT:SAMs, among which PEDOT:PSS is a water-dispersed solution purchased from Xi'an Yuri Solar Energy Co., Ltd. and used directly after filtration without any additional treatment. The test was conducted without adding any free radical scavenger or any external free radical excitation means. It can be seen that there is no free radical signal in pure PEDOT and SAMs, but free radical signals attributed to lone pairs of electrons appear in PEDOT:PSS and PEDOT:SAMs. In the absence of a scavenger, the appearance of this signal can only indicate that the PEDOT molecule stabilizes the deprotonated acid radicals of PSS and SAMs, which indicates that the binding mode of PEDOT:SAMs is a coordination binding similar to that of PEDOT:PSS. In addition, PEDOT:SAMs has a stronger signal, which indicates that its charge transfer ability is higher than that of PEDOT:PSS.
[0075] Example 2
[0076] A method for preparing a perovskite solar cell assembly comprises the following steps.
[0077] (1) Hole transport layer mother solution: 200 μL of the reaction solution obtained in Example 1 was taken out, added to 800 μL of ethanol for dilution, and then filtered after sufficient shaking and stirring to obtain a hole transport layer mother solution.
[0078] (2) Preparation of perovskite precursor solution: 454.9 mg of lead iodide, 335.3 mg of tin iodide, 187 mg of FAI, 85.8 mg of MAI, 47 mg of CsI, and 14.1 mg of tin fluoride were added to a vial, and then 750 μL of DMF and 250 μL of DMSO were added, and the mixture was shaken and stirred thoroughly until a bright yellow clear oily liquid was formed. The obtained oily liquid was filtered and set aside.
[0079] (3) Preparation of electron transport layer solution: Dissolve 25 mg of PCBM powder in 1 mL of chlorobenzene, shake thoroughly for ten minutes, and filter for later use.
[0080] (4) Preparation of hole blocking layer solution: Dissolve 2 mg of BCP powder in 1 mL of isopropanol, shake thoroughly for ten minutes, and filter for later use.
[0081] (5) Preparation of hole transport layer: Take a pre-etched ITO glass sheet, clean it with water, ethanol, acetone, and isopropanol ultrasonically in turn, and clean its surface with a plasma cleaner. Transfer the cleaned ITO glass sheet to the spin coating device, add 50 μL of the hole transport layer mother solution, and perform the spin coating operation according to the parameters of final speed 3000 rpm, acceleration 2000 rpm, and spin coating time 30 seconds. After the spin coating is completed, anneal the ITO glass sheet coated with PEDOT:SAMs at 100°C on a constant temperature hot plate for ten minutes.
[0082] (6) Preparation of perovskite active layer: Transfer the annealed ITO glass sheet coated with the hole transport layer to the glove box, drip 55 μL of the perovskite precursor solution on it, and perform spin coating: 1. Speed 1000 rpm, duration 5 s, acceleration 200 rpm / s; 2. Speed 4000 rpm, duration 60 s, acceleration 1000 rpm / s; 3. Speed 6000 rpm, duration 2 s, acceleration 1000 rpm / s. Within 15-25 seconds after the start of the second step of the program, drip 150 microliters of ethyl acetate onto the ITO to promote crystallization. After the spin coating process is completed, transfer the ITO to a constant temperature hot plate and anneal at 100°C for ten minutes.
[0083] (7) Preparation of electron transport layer: After annealing, further spin-coat the electron transport layer: 35 μl of electron transport layer solution was added to the ITO and spin-coated at a speed of 1200 rpm, a duration of 30 s, and an acceleration of 1000 rpm / s. After spin coating, the ITO was transferred to a constant temperature hot plate and annealed at 70° C. for 5 minutes.
[0084] (8) Preparation of hole blocking layer: After annealing, further spin coating the hole blocking layer: 50 μL of hole blocking layer solution was added to ITO by dynamic spin coating, and the spin coating parameters of dynamic spin coating were: rotation speed 4000 rpm, duration 30 s, acceleration 2000 rpm / s, and the hole blocking layer solution was added immediately after the spin coating process started. After the spin coating was completed, the ITO was transferred to a constant temperature hot plate and annealed at 70 degrees Celsius for 1 minute.
[0085] (9) Preparation of electrode layer: After annealing, the obtained sample is transferred to a resistive vacuum thermal evaporation device, and 150 nm thick copper is evaporated as an electrode to obtain the final perovskite solar cell module.
[0086] In order to demonstrate the superior effect of PEDOT:SAMs as a hole transport layer for the device, the stability and IV curve tests of the prepared devices were carried out. To ensure the credibility of the results, statistical charts were used to compare the performance.
[0087] Fig.10The IV curve test results of the perovskite device obtained when SAM, PEDOT, PEDOT:PSS, and PEDOT:SAMs were used as the hole transport layer were compared. It can be seen that the average open circuit voltage of PEDOT:PSS is 0.85V, which is higher than 0.81V of PEDOT, 0.78V of PEDOT:PSS and 0.82V of SAM, indicating that it has a more matched energy level and a better interface, thus reducing the open voltage loss. The average efficiency of PEDOT:SAMs reached 21.3%, which is also the highest among the four samples.
[0088] Fig.11 This is a test of the storage stability of perovskite devices obtained when PEDOT:PSS and PEDOT:SAMs were used as hole transport layers in a N2 environment. The device using PEDOT:PSS lost almost half of its efficiency within 150 hours, while the device using PEDOT:SAMs was still able to maintain about 90% of its initial efficiency after 500 hours of storage, which shows that PEDOT:SAM plays a significant role in improving device stability.
[0089] Fig.12 The performance of transport layers with different ratios prepared by using 200μL EDOT (6mmol) and different amounts of SAMs (MEO-2PACz) in solar cell devices. It can be seen that with the change of the amount of SAMs added, the target device opening voltage will show a certain regular change. Therefore, the process that best suits the target material can be selected by changing the ratio.
[0090] Fig.13 The performance of the transport layer prepared by heating 200μL EDOT (6mmol) and 3mg SAMs (MEO-2PACz) at 130 degrees Celsius for different time in the solar cell device. Prolonging the heating time can improve the device performance within a certain range, and the optimal heating time needs to be adjusted according to the actual use.
[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A conductive material, characterized in that: It includes: PEDOT and SAMs molecules; The PEDOT and the SAMs molecules are coordinated and bound to each other.
2. The conductive material according to claim 1, characterized in that The raw materials for preparing the conductive material include EDOT molecules and SAMs molecules; the molar ratio of the EDOT molecules to the SAMs molecules is 1:0.1-50; Optionally, the molar ratio of the EDOT molecules to the SAMs molecules is 10 to 30:
3.
3. The method for preparing a conductive material according to claim 1 or 2, characterized in that: It includes: It is prepared using EDOT molecules and SAMs molecules.
4. The preparation method according to claim 3, characterized in that: The preparation method comprises the following steps: Mixing the EDOT molecules and the SAMs molecules in a solvent to obtain a mixed solution; The mixed solution is heated to react to obtain a conductive material.
5. The preparation method according to claim 4, characterized in that: The heating reaction conditions include: 12 to 240 hours, 70 to 180° C.; Optionally, the heating reaction conditions include: 12 to 48 hours, 130 to 180°C.
6. The preparation method according to claim 4, characterized in that: The SAMs molecules include any one or more combinations of MEO-2PACz, 3-(9H-carbazole-9-yl) propionic acid, 9-carbazoleacetic acid and 2PACz.
7. The preparation method according to claim 4, characterized in that: The solvent includes any one or more combinations of DMF, DMSO, water, methanol, ethanol and ethyl acetate.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The mixing method includes: stirring; Optionally, the stirring speed is 100 to 1500 rpm; Optionally, the stirring time is 0.1 to 120 hours; Optionally, the stirring temperature is 0 to 100° C.; Optionally, when performing the heating reaction, the preparation method further comprises stirring the mixed solution at a constant temperature; Optionally, the constant temperature stirring speed is 1 to 4000 rpm.
9. Use of the conductive material according to claim 1 or 2 or the conductive material prepared by the preparation method according to any one of claims 3 to 8 in the preparation of perovskite cells or perovskite cell components.
10. A perovskite battery or a perovskite battery assembly, characterized in that: The perovskite battery comprises: a conductive substrate, a hole transport layer, a perovskite active layer, an electron transport layer, a hole blocking layer and an electrode layer; wherein the hole transport layer is prepared using the conductive material as claimed in claim 1 or 2 or a conductive material prepared by the preparation method as claimed in any one of claims 3 to 8.
Citation Information
Patent Citations
Polyphosphocarbazole material, preparation method and application in photoelectric device
CN117050277A
Method for preparing perovskite film layer, perovskite film layer, and solar cell
WO2024187424A1